Physical activity as a prescription for diabetic retinopathy - Poborowska, Dominika; Kahan, Weronika; Polańska, Katarzyna; Najjar, Oliwia; Wojaczek, Marta; Bąk, Emilia; Szafrańska, Weronika; Fordymacki, Jacek; Gańko, Tomasz (Quality in Sport, 2024)
Introduction and purpose Diabetic retinopathy is one of the leading causes of vision loss in diabetic patients. The purpose of this work is to confront the problem of retinopathy and present the beneficial effects of physical activity on retinal health in patients in this risk group. State of knowledge This paper reviews the literature on the problem of microangiopathic complications of diabetes, diabetic retinopathy, and the effect of physical activity on changing the incidence of this complication. According to the WHO, diabetic retinopathy is the leading cause of preventable blindness and visual impairment. Trends in diabetes and its associated complications are steadily increasing. Diabetic retinopathy occurs in about one-third of diabetics. It can be prevented by controlling blood glucose, blood pressure and lipid levels. Following a proper diet and physical activity can maintain adequate glucose levels, thereby reducing the incidence of diabetes complications. Material and method The literature available on Google Schoolar and "PubMed" was reviewed. The focus was on presenting the problem of microangiopathic complications of diabetes mellitus detailing diabetic retinopathy, diagnosis, treatment methods, pathogenesis of the condition and prevention of this complication through the beneficial effect of regular physical activity in diabetic patients. Summary Our review succeeded in presenting the current status of the problem of retinopathy, the development of diagnosis and treatment of diabetic retinopathy. On the basis of a number of studies presented in this review, we managed to prove the positive aspect of physical exercise on prevention, treatment and reduction of the effects and complications of diabetes. In our review, we concluded that increasing physical activity in daily lifestyle is one of the methods of treating diabetes by lowering blood glucose levels, thereby reducing the risk of diabetic retinopathy as a complication of diabetes.